Sloterdijk: mystische y antropología; el desierto y la emergencia del humano potencial de traslado - Vásquez Rocca, Adolfo (Nómadas. Critical Journal of Social and Juridical Science, 2009)
That certain individuals began to appear to countermarch of the schemes of their culture and would be able to issue slogans of negation to cosmic normality, is something that can be understood more easily if we interpreted the historicidad of the three last millenia as the emergencia of the potential human of transfer. One extends on the Earth, from India to Ireland, an ascetic belt, scene of a mighty secession of word normality.